PERAN GURU PPKn DALAM MENANAMKAN JIWA NASIONALISMEN TERHADAP SISWA KELAS VIII SMP NEGERI 1 ONOHAZUMBA KABUPATEN NIAS SELATAN - Suanima Bu’ulolo (Universitas Nias Raya, 2023)
Nationalism is an understanding (teaching) to love the nation and its country or the awareness of one nation, which actually together achieves, maintains and maintains and serves the identity, integrity, prosperity and strength of the nation, the spirit of nationalism. The purpose of this study was to determine the role of Civics teachers in instilling a spirit of nationalism in SMP 1 Onohazumba students at the Southern State Council and to determine the supporting and inhibiting factors for the role of the civics teacher in introducing national blessings in . students Research methods with qualitative descriptive methods. Data collection techniques through observation, interviews and documentation. Data analysis techniquesusing the steps of data reduction, data display, inference and verification. material validity using observation, triangulation, peer review persistence through discussion. The results of this study indicate that the teacher's role in instilling a spirit of nationalism in students is to set an example and lead especially in ceremonies and morning meetings. Barriers to the role of the PPKn teacherin instilling a national spirit in students is the lack of national spirit education material according to the curriculum, so teachers must look for other material related to instilling a national spirit, for example. for example the material about the pillars of the state. One of the supporting factors for the teacher's role in introducing a sense of nationality among students is the existence of counseling activities aimed at each student, where students are invited to find out the nature and character of these students one by one. Regarding the suggestions that researchers can give, namely always trying to improve activities related to the national spirit by providing instructions on the benefits of the activities practiced so that students understand the meaning of national spirit and attitude.